2020
DOI: 10.3389/fcell.2020.00601
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of FGF Signaling Ameliorates Inflammatory Response in Hepatic Stellate Cells

Abstract: It is a well-documented event that fibroblast growth factors (FGFs) regulate liver development and homeostasis in autocrine, paracrine, and endocrine manners via binding and activating FGF receptors (FGFRs) tyrosine kinase in hepatocytes. Recent research reveals that hepatic stellate cells (HSCs) play a fundamental role in liver immunology. However, how FGF signaling in HSCs regulates liver inflammation remains unclear. Here, we report that FGF promoted NF-κB signaling, an inflammatory pathway, in human HSCs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…Our data indicate that exposure of cultured HSCs to recombinant epiregulin accelerated the production of pro-fibrogenic genes ( Figure 3 ). This is consistent with previously reported observations that other members of the EGF family including EGF ( Lin and Chen, 2008 ), heparin-bound EGF (HB-EGF) ( Takemura et al, 2013 ), FGF ( Wang et al, 2020 ), and amphiregulin ( Perugorria et al, 2008 ) all contribute to HSC trans-differentiation and liver fibrosis. Of note, all four EGF ligands signal through the same receptor (EGFR) ( Riese and Cullum, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our data indicate that exposure of cultured HSCs to recombinant epiregulin accelerated the production of pro-fibrogenic genes ( Figure 3 ). This is consistent with previously reported observations that other members of the EGF family including EGF ( Lin and Chen, 2008 ), heparin-bound EGF (HB-EGF) ( Takemura et al, 2013 ), FGF ( Wang et al, 2020 ), and amphiregulin ( Perugorria et al, 2008 ) all contribute to HSC trans-differentiation and liver fibrosis. Of note, all four EGF ligands signal through the same receptor (EGFR) ( Riese and Cullum, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…FGFR1 has also been shown to be widely expressed in the myofibroblasts of injured palates, suggesting that FGFR1 signaling is also important for palate repair during injury [ 8 , 36 ]. Finally, it has been demonstrated that disruption of FGFR1 signaling reduces local inflammation by restraining activation of the NF-κB signaling cascades [ 37 , 38 ]. Clearly, FGFR1 plays a key role in maintaining normal development processes and in preventing fibrosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the bFGF/FGFR1 axis can exert an anti-inflammatory response in astrocyte-mediated neuroinflammation, especially after infrasound exposure [ 54 ]. However, other authors have reported that the axis exerts a pro-inflammatory effect [ 38 , 40 , 55 ]. Hence, in the case of orofacial clefts, we postulate that this axis indeed exerts a pro-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Quiescent HSCs are vitamin A-storing cells located in the perisinusoidal space near the sinusoid endothelial cells (SEC) and hepatocytes (6). Hepatic stellate cells can become activated due to chemokines and cytokines released during liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) can induce severe inflammation and enhance fibrosis in liver damage models (11). Treating human HSCs with LPS dramatically activates the inflammatory signaling pathway and aggravates the accumulation of proinflammatory chemokines (6). A20 is an intracellular ubiquitin-editing enzyme that has been shown as a crucial hepatoprotective factor to prevent chronic liver inflammation (12).…”
Section: Introductionmentioning
confidence: 99%